Challenges of Endovascular Treatment in Patients With “False” Left Main Coronary Bifurcation Lesions - D. A. Maximkin; S. K. Loginova; Sh. Sh. Fatulloeva (Инновационная медицина Кубани)
We discuss main challenges of much-debated endovascular treatment in patients with “false” bifurcation stenoses of the left main coronary artery. There are no convincing literature data on the rationale of planning complete bifurcation stenting using 2 stents and clear indications for this procedure. We highlight the importance of studying the effectiveness and safety of the complex routine use of various intravascular imaging during the left main coronary artery percutaneous coronary intervention. We analyzed observations in which a “false” bifurcation lesion can only be considered an ostial stenosis, which will affect the stenting strategy. We focus on the development of universal algorithms for performing endovascular interventions, including those using intravascular imaging which role at each stage of surgery should be additionally studied.